2011
DOI: 10.1253/circj.cj-11-0350
|View full text |Cite
|
Sign up to set email alerts
|

Time in the Therapeutic Range During Warfarin Therapy in Japanese Patients With Non-Valvular Atrial Fibrillation - A Multicenter Study of Its Status and Influential Factors -

Abstract: Background: Time in the therapeutic range (TTR) assesses the appropriateness of international normalized ratio of prothrombin time (PT-INR) control during warfarin therapy. We examined the status of and the factors influencing TTR in Japanese patients with non-valvular atrial fibrillation (AF). Methods and Results:We enrolled 501 AF patients (mean age, 70±10 years; males 66%; mean CHADS2 score 2.0±1.2) taking warfarin for ≥2 years from 5 prefectures. The PT-INR therapeutic range was set up according to the 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 23 publications
6
36
1
1
Order By: Relevance
“…This may also mean that the time in the therapeutic range (TTR) in generally higher in Japan than other countries [17,18]. The previous Japanese guideline for pharmacotherapy of AF (JCS of NOAC treatment was the occurrence of adverse events, including bleeding events; this was similar to the findings for the Dresden cohort [8,11,12].…”
supporting
confidence: 68%
“…This may also mean that the time in the therapeutic range (TTR) in generally higher in Japan than other countries [17,18]. The previous Japanese guideline for pharmacotherapy of AF (JCS of NOAC treatment was the occurrence of adverse events, including bleeding events; this was similar to the findings for the Dresden cohort [8,11,12].…”
supporting
confidence: 68%
“…18 Okumura et al reported that the average TTR at 5 Japanese centers for cardiovascular disease was 64%. 10 These findings indicate the need for the establishment of strategies to improve TTR in actual clinical practice.…”
Section: Change In Ttrmentioning
confidence: 97%
“…During follow-up, warfarin dosage for patients with non-valvular AF was adjusted according to the Japanese Guidelines for Pharmacotherapy of Atrial Fibrillation to maintain INR at 2.0-3.0 and 1.6-2.6 for patients aged <70 years and ≥70 years, respectively. 10 Warfarin dosage for patients with mechanical heart valve(s) and mitral stenosis was also adjusted according to the Guidelines to maintain INR at 2.0-3.0. 10 For the present study, we used the PT-INR results obtained at least 3 months after the initiation of warfarin.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations